Validation of Experts to the Module Writing Short Text Based on Character Education in Class XI Students of SMA Negeri 1 Pangkalan Susu - Liza Wiwita; Marice; Wisman Hadi (Britain International for Academic Research (BIAR) Publisher, 2020)
The aim of this research is to validate of experts to the module writing short text base on character education. This research method uses the Research and Development (R&D) method (in Tegeh, et al, 2014: 7) saying that research and development methods are research methods used to produce certain products and test the effectiveness of certain products. The result is Material expert validation on content eligibility assessment is in very valid criteria with an average value of 85%. Feasibility of presentation is very valid criteria with an average value of 90%, and language eligibility is very valid criteria with an average value of 87%.